Germination of Dypsis decaryi seeds under salt stress - Vieira, Guilherme Rodrigues [UNESP]; de Souza, Antonio Maricélio Borges; Campos, Thiago Souza [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP] (My University, 2023)
The triangle palm (Dypsis decaryi), a species native to Madagascar, possesses various ornamental characteristics that make it highly valued in the international market. Seed propagation is the primary method for its cultivation, and this process is influenced by factors such as sowing time and salinity. In this study, we aimed to investigate the germination behavior of D. decaryi seeds under different saline concentrations of sodium chloride (NaCl) and potassium chloride (KCl), in two distinct periods. The experiment followed a completely randomized design, employing a 2 × 2 × 5 factorial arrangement corresponding to two seasons of experimentation (summer and winter), two salt types (NaCl and KCl), and four salt concentrations (25, 50, 75, and 100 mM), in addition to a control group without salt. Each treatment consisted of four replications, with 25 seeds per replication. The evaluated parameters were germination percentage, germination speed index, and mean germination time. No significant effects were observed when analyzing the salt types individually, the interaction between seasons and salts, or the interaction between all three factors. However, during the summer season, the seeds exhibited higher mean germination percentages and germination speed indices and shorter mean germination times, regardless of the salt used. A high germination percentage (73.79%) was observed at the highest salt concentration tested for both NaCl and KCl. Consequently, we conclude that D. decaryi is tolerant to salinity, as simulated by KCl and NaCl, during the seed germination process. Sowing time, salt concentrations, and the interaction between these variables influenced germination.
Germinação de sementes de Dypsis decaryi submetidas ao estresse salino
Keywords: Abiotic Stress; Arecaceae; KCl; NaCl; Ornamental plant; Plant propagation